2002
DOI: 10.1055/s-2002-33549
|View full text |Cite
|
Sign up to set email alerts
|

Infektionen und Erkrankungen nach Fernreisen

Abstract: Most of the travel-associated infections are self-limited. In case of fever, malaria and potentially hemorrhagic fever should be excluded and be followed by a stepwise investigation on the cause of fever. In case of diarrhea, parasitologic investigations should be performed by an experienced laboratory and fresh stool samples should be used. Intensive co-operation will be necessary between physician, pharmacists and others active in the field of travel medicine in order to address the shortcomings in chemoprop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…In addition, sample inhibition is not the only challenge for nucleic acid extraction. When stool samples from the tropics are assessed, the diagnostic focus is rarely on bacterial pathogens alone, but parasitic infectious agents are frequently also targeted [ 56 , 57 , 58 ]. In order to release nucleic acids from strong-shelled eggs or cuticle cells of helminthic parasites, harsh nucleic acid extraction methods, i.e., freeze-thawing at the very least [ 59 ] but also more robust, bead beating-based extraction schemes [ 60 , 61 ] have been suggested, although their superiority in terms of sensitivity has not been continuously demonstrated [ 62 ].…”
Section: Nucleic Acid Extraction–challenges For a “One-size-fits-all” Solutionmentioning
confidence: 99%
“…In addition, sample inhibition is not the only challenge for nucleic acid extraction. When stool samples from the tropics are assessed, the diagnostic focus is rarely on bacterial pathogens alone, but parasitic infectious agents are frequently also targeted [ 56 , 57 , 58 ]. In order to release nucleic acids from strong-shelled eggs or cuticle cells of helminthic parasites, harsh nucleic acid extraction methods, i.e., freeze-thawing at the very least [ 59 ] but also more robust, bead beating-based extraction schemes [ 60 , 61 ] have been suggested, although their superiority in terms of sensitivity has not been continuously demonstrated [ 62 ].…”
Section: Nucleic Acid Extraction–challenges For a “One-size-fits-all” Solutionmentioning
confidence: 99%
“…Improving prophylactic measures is the only way to reduce the incidence of malaria cases in Germany (Schoneberg et al, 2001). Unfortunately, compliance and correct use of prophylactic drugs is regret-tably low (not only among German travelers but among those of many countries); Harms et al (2002) found that among the patients at a travel medicine clinic in Berlin, only 34% of the returnees from malaria-endemic areas had taken chemoprophylaxis. In instances of travel to Africa and Asia, chemoprophylaxis corresponded to international standards in only 48 % and 23% of cases respectively, illustrating the reason for the large number of malaria cases among travelers.…”
Section: Germanymentioning
confidence: 99%
“…B. Ciprofloxacin zweimal 500mg täglich über 1-3 Tage bzw. bis zur Besserung der Symptome), um die Krankheitsdauer zu verkürzen und eventuellen Komplikationen vorzubeugen (3). Bereits eine Einmaldosis von 500mg Ciprofloxacin (Beginn nach drei Durchfällen) erwies sich bei der unkomplizierten Reisediarrhoe zur Verkürzung der Krankheitsdauer als wirksam (auf durchschnittlich 21h vs. 50h bei Placebo) (6).…”
Section: Chemotherapieunclassified